Efektivitas Media Promosi Kesehatan Mengenai Dampak Merokok pada Siswa SMA 11 Kota Jambi - Adriaswara, Muhammad Rivansyah; Aurora, Wahyu Indah Dewi; Kusdiah, Erny (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effectiveness of promotional media regarding the impact of smoking on the health of students at SMA 11 in Jambi City. Quantitative eikspeirimeintal research with a pretest and posttest design was used, with 30 questions that had been tested for validity and reliability. Data were analyzed using univariate and bivariate. The results showed that there were differences in pre-test and post-test knowledge in both health promotion system groups, where the respondent group with counseling was more effective than educational videos. in students at SMA 11 in Jambi City.